Fault geometry and mechanics of marly carbonate multilayers: An integrated field and laboratory study from the Northern Apennines, Italy. (December 2016) - Giorgetti, C.; Collettini, C.; Scuderi, M.M.; Barchi, M.R.; Tesei, T.
Abstract: Sealing layers are often represented by sedimentary sequences characterized by alternating strong and weak lithologies. When involved in faulting processes, these mechanically heterogeneous multilayers develop complex fault geometries. Here we investigate fault initiation and evolution within a mechanical multilayer by integrating field observations and rock deformation experiments. Faults initiate with a staircase trajectory that partially reflects the mechanical properties of the involved lithologies, as suggested by our deformation experiments. However, some faults initiating at low angles in calcite-rich layers ( θ i = 5°–20°) and at high angles in clay-rich layers ( θ i = 45°–86°) indicate the important role of structural inheritance at the onset of faulting. With increasing displacement, faults develop well-organized fault cores characterized by a marly, foliated matrix embedding fragments of limestone. The angles of fault reactivation, which concentrate between 30° and 60°, are consistent with the low friction coefficient measured during our experiments on marls ( μ s = 0.39), indicating that clay minerals exert a main control on fault mechanics. Moreover, our integrated analysis suggests that fracturing and faulting are the main mechanisms allowing fluid circulation within the low-permeability multilayer, and that its sealing integrity can be compromised only by the activity of larger faults cutting across its entire thickness. Highlights: Field and laboratory data integrated to investigate faulting in clay-rich multilayers. Fault initiation controlled by lithological strength and pre-existing anisotropies. Fluid flow within low-permeability multilayers controlled by faulting.